Short Stereoselective Synthesis of the Phytophthora Universal Mating Hormone α1 Using Lithiation/Borylation Reactions1. Issue 17 (14th March 2014) - Pulis, Alexander P.; Fackler, Philipp; Aggarwal, Varinder K.
Abstract The universal mating hormone α 1 of the virulent plant pathogen Phytophthora has been synthesized in 12 steps and 28 % overall yield. Key CC bond‐forming steps involved the use of two lithiation/borylation reactions to couple together enantioenriched building blocks, one of which also set up the stereochemistry of the tertiary alcohol at C11. Detailed analysis showed that the diastereomeric purity of the target molecule was >91 %, the highest obtained to date.